2009
DOI: 10.1182/blood-2009-06-189209
|View full text |Cite
|
Sign up to set email alerts
|

How I treat ADA deficiency

Abstract: Adenosine deaminase deficiency is a disorder of purine metabolism leading to severe combined immunodeficiency (ADA-SCID). Without treatment, the condition is fatal and requires early intervention. Haematopoietic stem cell transplantation is the major treatment for ADA-SCID, although survival following different donor sources varies considerably. Unlike other SCID forms, 2 other options are available for ADA-SCID: enzyme replacement therapy (ERT) with pegylated bovine ADA, and autologous haematopoietic stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
208
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(212 citation statements)
references
References 48 publications
2
208
0
1
Order By: Relevance
“…However, more favorable results have been reported in other patients. 7 The data from P2 are encouraging, also regarding the lung disease observed in some ADA-deficient patients. 4 We believe that ERT also has an important role in patients diagnosed beyond infancy, mainly to prevent the development of comorbidities that increase the risk for stem cell transplantation.…”
Section: To the Editormentioning
confidence: 85%
See 1 more Smart Citation
“…However, more favorable results have been reported in other patients. 7 The data from P2 are encouraging, also regarding the lung disease observed in some ADA-deficient patients. 4 We believe that ERT also has an important role in patients diagnosed beyond infancy, mainly to prevent the development of comorbidities that increase the risk for stem cell transplantation.…”
Section: To the Editormentioning
confidence: 85%
“…5,6 While ERT is a generally accepted treatment in ADA-SCID to stabilize patients prior to stem cell transplantation, its use in patients with a later onset of the disease is less well documented. 7 Although initial immune reconstitution can be observed in most patients receiving ERT, several develop neutralizing antibodies against the bovine-derived ADA, which can completely reverse immune recovery. 8 Fortunately, in P2 and other patients, it has been possible to overcome this problem by increasing the dose.…”
Section: To the Editormentioning
confidence: 99%
“…Haematopoietic stem cell transplantation is today the gold standard treatment for ADA-SCID, although it is dependent on a good donor match [9]. ERT with polyethylene glycol-modified bovine adenosine deaminase (PEG-ADA, Adagen ® ) is available and determines the elimination of toxic metabolites and a good reconstitution of the immune system [10].…”
Section: Abbreviationsmentioning
confidence: 99%
“…10,11 We have recently shown that it is possible to identify patients with ADA-SCID using tandem mass spectrometry (tandem-MS) on DBSs collected at birth during routine newborn screening procedures at a low cost (0.01V per test). 12 An expanded newborn screening including more than 40 metabolic diseases is now performed by using tandem-MS in many countries in the world, so that millions of children worldwide are screened each year for those diseases.…”
Section: Abbreviations Usedmentioning
confidence: 99%